The relationship between vitamin D levels and Alzheimer’s disease risk: insights from a centenarian study of Chinese women - Li, Yupeng; Wang, Xujie; Yu, Mei; Wang, Fei; Song, Dong; Liu, Musong; Liang, Xu; Liu, Hongzhou; Liu, Jiangbo; Fu, Shihui; Liu, Xuhui (Frontiers in Nutrition, 2025)
BackgroundWhile vitamin D₃ (VD₃) has been implicated in Alzheimer’s disease (AD) prevention, limited evidence exists among centenarians—particularly women—who exhibit unique cognitive aging trajectories. This study aimed to examine the association between serum 25-hydroxyvitamin D [25(OH)D] levels and AD risk in Chinese female centenarians.MethodsWe included 514 female participants aged ≥100 years from the China Healthy Longevity Multicenter Study (CHLMS). AD was diagnosed using education-adjusted MMSE thresholds and clinical exclusion of non-AD dementias. Serum 25(OH)D and biochemical markers were measured using standardized laboratory protocols. Logistic regression models (unadjusted and progressively adjusted) assessed associations between 25(OH)D and AD. Restricted cubic spline (RCS) and piecewise regressions evaluated non-linear and threshold effects, while subgroup analyses explored effect modification.ResultsHigher serum 25(OH)D levels were independently associated with lower odds of AD (adjusted OR per 1 ng/mL: 0.95; 95% CI: 0.90–1.00; p = 0.037). Compared to the lowest quartile, participants in the highest quartile had an 87% reduced risk (OR = 0.13; 95% CI: 0.03–0.50; p = 0.007). RCS analysis revealed a significant inverse dose–response relationship, with a potential threshold effect observed at 29.3 ng/mL. Piecewise regression confirmed that the protective association was strongest below this threshold. Subgroup analyses across smoking, hypertension, and early-life indicators showed consistent effects with no significant interactions.ConclusionAmong Chinese female centenarians, serum vitamin D₃ levels are inversely associated with AD risk in a dose-dependent manner, particularly below 29.3 ng/mL. These findings highlight the relevance of vitamin D₃ as a potentially modifiable factor in cognitive aging and support further interventional studies in the oldest-old population.